On ranking decision making units using relative similar units in data envelopment analysis. (1st January 2014) - Nasseri, Seyed Hadi; Gholami, Omid; Ebrahimnejad, Ali
Data envelopment analysis (DEA) is a considerable mathematical programming technique for measuring the relative efficiencies of a set of decision making units (DMUs) with multiple inputs and multiple outputs. Conventional DEA assists decision makers in distinguishing between efficient and inefficient DMUs in a homogeneous group. However, it does not give more information about the efficient DMUs. In this paper, a new method is proposed to differentiae the performance of efficient units. In the proposed method a new DEA model is constructed by introducing some virtual units called relative similar units associated with efficient units into the possibility production set. We present two practical examples to demonstrate the applicability of the proposed method and to exhibit the efficacy of the procedures.